2014
DOI: 10.1002/anie.201402709
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Au–Bi2S3 Heteronanostructures

Abstract: Au-Bi2S3 heteronanostructure photocatalysts were designed in which the coupling of a metal plasmon and a semiconductor exciton aids the absorption of solar light, enhances charge separation, and results in improved catalytic activity. Furthermore, these nanostructures show a unique pattern of structural combination, with Au nanoparticles positioned at the center of Bi2S3 nanorods. The chemistry of formation of these nanostructures, their epitaxy at the junction, and their photoconductance were studied, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 43 publications
4
89
0
Order By: Relevance
“…The improved photocatalytic activity of semiconductor composites is attributed to a large extent to the enhanced separation of photoinduced electrons and holes via interfacial charge transfer [10,12,27e29]. Bismuth sulfide (Bi 2 S 3 ) is a semiconductor with a narrow band gap about 1.3 eV [30]. The narrow band gap and large absorption coefficient make it an ideal candidate for photoresponsive materials [31e33].…”
Section: Introductionmentioning
confidence: 99%
“…The improved photocatalytic activity of semiconductor composites is attributed to a large extent to the enhanced separation of photoinduced electrons and holes via interfacial charge transfer [10,12,27e29]. Bismuth sulfide (Bi 2 S 3 ) is a semiconductor with a narrow band gap about 1.3 eV [30]. The narrow band gap and large absorption coefficient make it an ideal candidate for photoresponsive materials [31e33].…”
Section: Introductionmentioning
confidence: 99%
“…5a. Gold nanoparticles have strong absorption peak among 510-600 nm (determined by the size, shape of Au NPs) due to surface plasmon resonance (SPR) [12,32,33]. The Au NPs-CdS NWs hybrids exhibit a broadened and redshift absorption peak comparing to Au NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The Au NPs-CdS NWs hybrids exhibit a broadened and redshift absorption peak comparing to Au NPs. The change is a sign that Au-CdS have formed well in metal-semiconductor heterostructure, because high dielectric coefficient and exciton-plasmon coupling of CdS can change the SPR peak of Au NPs [33,34]. For 20 nm Au NPs-CdS NWs hybrids with different amounts of Au NPs, the absorption of light (400-700 nm) is enhanced with the increase in the amount of Au NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Reasonable design of heterostructure prototypes has been devoted to developing next generation photoelectric and photovoltaic devices from a single NC. [14][15][16][17][18] However, limited research has been demonstrated on heterostructured NCs as ORR electrocatalysts. On the contrary, impelled by the advantages shown by low-dimensional quantum confi nement effects, [19][20][21][22][23] a variety of core-shell, dumb-bell, striped, and match-stick heterostructured NCs have been synthesized via colloidal chemistry routes in the past 15 years.…”
Section: Introductionmentioning
confidence: 99%